A Lived Body Affected by Motor Disability - Viluckienė, Jolita (Sociologija. Mintis ir veiksmas, 2017)
This article applies the body phenomenology perspective of M. Merleau-Ponty to explore how people with motor disability experience the lived world through their disabled bodies, and in what senses their relationship with the world – as well as with their body, which is also a part of the world – is coloured. Their personal narratives are based on qualitative in-depth interviews and suggest that disabilities acquired by people at later stages of their lives are experienced as certain disobediences of the body, i.e., the discrepancy between the intentions to move and the movement itself. The loss of tactile sensations in the separate parts of the body complicates the subject’s relationship with the world because, in the case of the non-sensitive areas of body, the contact with the world is indirect, i.e., created through some other part of the body as an intermediary. The individuals who possess a congenital disability or that have acquired it in childhood do not give any prominence to the disfunctionality of their body or to the limited capacity of movement and do not focus on the disability as a certain problem or a hindrance to their existence in the world; it is so because ever since their early age they are in constant contact with the world through the body affected by the disability. On the other hand, for them a physical disability is actualised in their interactions with other non-disabled corporeal subjects as well as in confrontations with the physical objects occurring in their living environments, which, due to their own disability, they are unavailable to dispose of.